2010
DOI: 10.1161/circulationaha.109.895037
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor Receptor–Associated Factor 1 (TRAF1) Deficiency Attenuates Atherosclerosis in Mice by Impairing Monocyte Recruitment to the Vessel Wall

Abstract: Background-Members of the tumor necrosis factor superfamily, such as tumor necrosis factor-␣, potently promote atherogenesis in mice and humans. Tumor necrosis factor receptor-associated factors (TRAFs) are cytoplasmic adaptor proteins for this group of cytokines. Methods and Results-This study tested the hypothesis that TRAF1 modulates atherogenesis in vivo. TRAF1Ϫ/Ϫ / LDLR Ϫ/Ϫ mice that consumed a high-cholesterol diet for 18 weeks developed significantly smaller atherosclerotic lesions than LDLR Ϫ/Ϫ (LDL re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 44 publications
(47 reference statements)
3
56
0
2
Order By: Relevance
“…Previous reports implicated TRAFs, specifically TRAF1 and -6, with the recruitment of leukocytes to inflamed tissue. [12][13][14] In accord with our data, So et al demonstrated that on induction of an asthma-like response TRAF5 deficiency aggravated airway inflammation. 32 This coincided (just as observed in our study) with enhanced expression of ICAM-1 on TRAF5-deficient ECs.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Previous reports implicated TRAFs, specifically TRAF1 and -6, with the recruitment of leukocytes to inflamed tissue. [12][13][14] In accord with our data, So et al demonstrated that on induction of an asthma-like response TRAF5 deficiency aggravated airway inflammation. 32 This coincided (just as observed in our study) with enhanced expression of ICAM-1 on TRAF5-deficient ECs.…”
Section: Discussionsupporting
confidence: 91%
“…23 At the end of the study, mice were harvested and histologically analyzed as described previously. 14,24,25 …”
Section: In Vivo Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Additional details of other TNF family receptor signaling, including IL-1R, TLR4 (similar to TLR2 signaling), and CD40 (similar to TNFR2) are presented in Only a few TRAF proteins have been targeted for knockout to study effects on atherosclerosis. Surprisingly, TRAF1 KO reduced atherosclerosis in LDLR null mice even though TRAF1 had been thought to inhibit TRAF2, particularly in TNFR2 signaling (1217). The apparently pro-atherogenic effect of TRAF1 may possibly be explained by observations on oligomer formation.…”
Section: The Noncanonical Pathway For Nf-b Translocationmentioning
confidence: 99%
“…To induce atherosclerosis, 6-week-old male mice were fed a Western diet (15% [w/w] fat and 0.25% [w/w] cholesterol, Research Diets) for 16 (aortic root analysis) or 24 (aorta en face analysis) weeks as previously described. 10,11 …”
Section: Generation Of Mact3 Transgenic Micementioning
confidence: 99%